Peran Pengurus Dalam Pembentukan Karakter Disiplin Santri Di Ma’had Mamba’ul Qur’an Munggang Wonosobo - Qurotul Aini; Ngarifin Shidiq; Vava Imam Agus Faisal (DAS Institute, 2024)
This study aims to evaluate the level of student discipline at the Ma’had Mamba'ul Qur'an Munggang Wonosobo Islamic boarding school, identify the role of the authorities in shaping students' disciplinary character, and determine the factors that influence the formation of disciplinary character at the school. The research uses a qualitative approach with the Field Research method, which involves collecting data through interviews, observation and documentation. Data analysis was carried out using the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of the research show that student discipline in participating in activities is not optimal, with some students not being disciplined and breaking the rules. For students who violate, sanctions or reprimands are given according to the type of violation. The role of administrators in shaping students' disciplinary character consists of three aspects: as a guide, as an educator, and as a friend. Each role has different tasks, remaining focused on building a disciplined character. Supporting factors in shaping students' disciplinary character include the continuity of a clear vision and mission of the school, strong cooperation between authorities, and quality performance from administrators. This factor influences the formation of students' disciplinary character positively.